A numerical study on thermal mixing in narrow channels inserted rectangular bodies - Kok, Besir; Firat, Mujdat; Öztop, Hakan Fehmi; Varol, Yasin (Pergamon-Elsevier Science Ltd, 2013)
A numerical study has been performed on thermal mixing phenomena in a narrow channel inserted with a body by twin-jets at different temperatures. The study is carried out for three jet Reynolds numbers (Re = 200, 400 and 600). Water is used as working fluid and the channel has an exit to supply continuity of mass. Governing equations are solved by using finite volume method. Adiabatic rectangular shaped objects at three different aspect ratios and locations are inserted into the channel to control thermal mixing as a passive technique. A thermal mixing index is defined and calculated from obtained values of temperatures for different parameters. Thus, results are presented with isotherms, streamlines and mixing index graphics for studied parameters. It is found that mixing performance increases in the first half of the channel (x/L = 0-0.5) with increasing of Re number. Also, it is decreased in the second half (x/L = 05-1) of the channel with higher values of Re number. The best mixing performance is formed for Case 3 at Re = 200 near the exit. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: Thermal mixing; Parallel jets; Heat transfer; CFD